Expression of lipoxin A4, TNFα and IL-1β in maternal peripheral blood, umbilical cord blood and placenta, and their significance in pre-eclampsia. (November 2014) - Dong, Wei; Yin, Lirong
<x xml:space="preserve">Abstract</x> Objective: The purpose of this study was to investigate the expression of lipoxin A4, TNFα and IL-1β in maternal peripheral blood, umbilical cord blood and placenta, and to assess their significance in pre-eclampsia. Methods: Ninty pregnant women were divided into three groups: a mild PE group (n = 30), a severe PE group (n = 30) and a control group (n = 30). We measured serum levels of lipoxin A4, TNFα and IL-1β using ELISA. Expression levels of lipoxin receptor (FPR2/ALX) mRNA were compared using quantitative RT-PCR. Results: Mean circulating levels of lipoxin A4, TNFα and IL-1β in the PE groups were significantly increased compared with matched women in the control group. The ratios of lipoxin A4/TNFα and of lipoxin A4/IL-1β in the PE groups were significantly decreased compared with matched women in the control group. No lipoxin A4 was detected in umbilical cord blood. There was a significant increase in FPR2/ALX mRNA expression in placenta obtained from the PE groups. Conclusions: The level of lipoxin A4 in maternal peripheral blood may correlate with the expression of FPR2/ALX in placenta. Lipoxin A4 increased to a lesser degree than either TNFα or IL-1β with progression of PE. This may be one of the reasons why oxidative stress and endothelial dysfunction in severe preeclamptic patients are much more serious that in cases of less severe preeclampsia. Moreover, lipoxin A4 does not have any effect on the fetus through the placenta. We conclude that supplementing with lipoxin A4 to ensure adequate levels may be a novel method for the treatment of pre-eclampsia without any effects on the fetus.